Ancient Latin Epics in Girolamo Vida's Christiad - Cianciosi, Stefano (Classical Studies E-Books Online, Collection 2025., 2025)
The Christiad (1535) is a Neo-Latin epic by the Italian Renaissance writer Girolamo Vida, based on the Gospels and written at the behest of Pope Leo X. Long seen as a Christian Aeneid, it emerges in this study as a far more complex work, demonstrating that while Virgil remains the main model, Vida also engages deeply with Lucretius, Ovid, Lucan, Silius Italicus, and Statius. By examining Vida's imitative techniques and integration of multiple epic models, this monograph reassesses the Christiad 's relationship with the ancient Latin epic tradition. In doing so, it sheds new light on the afterlife of these classical poems as print made them more widely available.